EFFECT OF SPORTS PARTICIPATION ON SELECTED CARDIOVASCULAR AND ADIPOSITY INDICES AMONG UNDERGRADUATE STUDENTS OF UNIVERSITY OF BENIN, EDO STATE (Journal of Biomedical Investigation, 2024)
Background: Participation in sporting activities produces a significant improvement in the physical, social and mental health of individuals and also reduce risk of diseases. Cardiovascular diseases are reported to be the leading cause of deaths worldwide, with an estimated 17.9 million people dying from cardiovascular related diseases in 2019.Aim: The aim of this study was to determine the effect of sport participation on selected cardiovascular health and adiposity indices among a cohort of undergraduate students.Methods: Consecutive sampling technique was used to recruit 359 consenting undergraduates of University of Benin. Data were obtained using the International Physical Activity Questionnaire. Participants were classified as non-sports participants, minimally active and very active sports participants. Descriptive statistics of mean, frequency, standard deviation and inferential statistics of ANOVA test were used to summarize and analyze the obtained data. The level of significance was set at 0.05.Results: Majority of the respondents were involved in sports activities (66.3%) while 33.7% were not involved in sporting activities. Among those involved in sports, 33.4% were classified as very active participants while 32.0% were minimally active. The results also revealed a significant difference in the systolic blood pressure, diastolic blood pressure, heart rate and respiratory rate of respondents among the three classified sport participation categories (p < 0.05 in all cases).Conclusion: Active participation in sports should therefore be encouraged among undergraduates’ students. Participation in sports seems to have a potential positive influence on cardiovascular, adiposity and respiratory functions.
Keywords: sports participation; cardiovascular; physical activity